2001
DOI: 10.1038/sj.leu.2402293
|View full text |Cite
|
Sign up to set email alerts
|

Clinical importance of interphase cytogenetics detecting occult chromosome lesions in myelodysplastic syndromes with normal karyotype

Abstract: At diagnosis, approximately half of myelodysplastic (MDS) patients presents a normal karyotype by conventional cytogenetic analysis (CCA). Fluorescent in situ hybridization (FISH) is more sensitive than CCA allowing for the detection of minor clones and of submicroscopic lesions. We have analyzed by FISH 101 MDS patients with normal karyotype for the occurrence of the abnormalities which are most frequently observed in MDS (ie ؊5/5q؊, ؊7/7q؊, ؉8, 17p؊). In 18 patients, 15 to 32% of interphase cells were found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
51
3
6

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 27 publications
5
51
3
6
Order By: Relevance
“…Our results are in agreement with those of previous studies (Table 4) in which the FISH technique detected the 5q deletion in 0% to 14% of cases. [16][17][18][19][20][21][22] The percentage of 5q-detection differed depending whether metaphases or interphase nuclei were studied. This could be related to a different rate of mitoses in cells carrying or not the 5q deletion.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in agreement with those of previous studies (Table 4) in which the FISH technique detected the 5q deletion in 0% to 14% of cases. [16][17][18][19][20][21][22] The percentage of 5q-detection differed depending whether metaphases or interphase nuclei were studied. This could be related to a different rate of mitoses in cells carrying or not the 5q deletion.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have reported on the ability of FISH to reveal masked karyotype defects. [24][25][26][33][34][35][36][37][38][39][40][41] Some have demonstrated that CC and FISH detect chromosome abnormalities at a similar frequency in MDS/AML patients and have concluded that CC is an excellent technique for identifying the most common chromosome defects in these patients, whereas FISH on interphase or mitotic cells has only limited utility. 29,39,40 In contrast, other studies have pointed out that FISH identifies minor clonal cell populations marked by À7 or by other structural defects in a significant number of CC normal patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some FISH studies have already shown that occult defects (mainly monosomy 7, trisomy 8, deletions of the long arm of chromosome 5 or of chromosome 7) may be detected in chromosomally normal MDS. [19][20][21][22][23][24][25][26][27][28] In addition, those reports suggested that FISH is a convenient complement to CC and have tried to define the most accurate 'FISH panel testing' for the analysis of chromosomally normal patients. [29][30][31] In the present study, we have performed FISH with seven single locus and four alphoid probes for the most frequent MDS chromosome aberrations in 57 patients, who were considered cytogenetically normal after the analysis of more than 20 metaphases.…”
Section: Introductionmentioning
confidence: 99%
“…Rigolin et al (3) analyzed 101 patients with primary MDS and a normal karyotype and observed 15-32% of interphase cells with at least one FISH abnormality. In that study, FISH abnormalities were associated with a higher rate of progression to AML (13/18 vs 12/83) and were predictive of a worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have stated that the frequency of chromosomal abnormalities is underestimated with conventional techniques such as G-banding because the aberrant clone does not proliferate well in cell cultures, reducing the possibility of detection (3)(4)(5). It has also been proposed that hidden clones not detected by conventional cytogenetics might be involved in the progression to acute leukemia of MDS cases with a normal karyotype (6,7), and that other, more sensitive approaches such as interphase fluorescent in situ hybridization (I-FISH) would be required for detection of occult lesions.…”
Section: Introductionmentioning
confidence: 99%